Using Users Profiling to Identifying an Attacks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays crime activities have increased in almost all areas, but this paper only focuses on who performs illegal activities within the organization. A user may perform insider and phishing attacks in the organization. A legitimate user of an organization may try to login in the administrator id, and then perform some illegal activities. Due to these activities, sensitive data can be modified or corrupted. Identification of illegal user’s behavior is very difficult within the organization. The scope  of this work is to analyze the log files, to filter out the user profiles of those who are involved in suspicious activity and to detect the suspicious activity of the user. In any organization, large number of log files is being generated, log manger system helps to take an optimal solutions. Although, a variety of log supervisor gadget exists, however, they are not providing that much efficiency. This paper analyses the ELK stack working principles and compare it with Splunk. ELK stack include many additional features such as indexing, preprocessing a large amount of  logs and producing graphical representation output using kibana.